2014
DOI: 10.1111/jace.13277
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Lithium Molybdate Ceramic Fabricated at Room Temperature

Abstract: Lithium molybdate disks were fabricated by moistening watersoluble Li 2 MoO 4 powder with deionized water and compressing it under a pressure of 130 MPa. Disks were postprocessed at room temperature, at 120°C, and at 540°C, which is a common sintering temperature for Li 2 MoO 4 . Regardless of the postprocessing temperature, densities as high as 87%-93% of the theoretical value were achieved. The X-ray diffraction patterns of processed disks were all the same with no signs of hydrates or constitutional water. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 8 publications
0
89
0
Order By: Relevance
“…The driving force of the consolidation of the Li 2 MoO 4 in the RTF method is pressure 21 which in the case of extrusion depends on the paste rheology, the extrusion rate, and the dimensions and the geometry of the dispenser 31 . Immediately after deposition of the paste, consolidation continues with the aid of the liquid phase and related capillary forces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The driving force of the consolidation of the Li 2 MoO 4 in the RTF method is pressure 21 which in the case of extrusion depends on the paste rheology, the extrusion rate, and the dimensions and the geometry of the dispenser 31 . Immediately after deposition of the paste, consolidation continues with the aid of the liquid phase and related capillary forces.…”
Section: Discussionmentioning
confidence: 99%
“…For microwave devices, Li 2 MoO 4 is of interest because of its beneficially low dielectric loss in addition to its low sintering temperature of 540 °C 19,20 . However, Li 2 MoO 4 is water-soluble, enabling component manufacture at temperatures as low as room temperature 2124 . In this method, referred to as room temperature fabrication (RTF), Li 2 MoO 4 powder is moistened with water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ULTCC, microwave dielectric ceramics can be densified without sintering aids since they are fabricated from intrinsically low melting point oxides. [10][11][12][13][14] [19] reported that dense ceramics can be obtained by …”
Section: Introductionmentioning
confidence: 99%
“…One of these materials is microwave dielectric lithium molybdate (Li 2 MoO 4 ) which is conventionally densified by sintering at 540°C and which exhibits a relative permittivity (ε r ) of 5.5 and a dielectric loss value (tan δ) of 0.00028 at 13.051 GHz . To decrease fabrication temperatures even further, a novel method for room‐temperature densification of Li 2 MoO 4 has recently been presented, based on the water solubility of Li 2 MoO 4 . Densification of the Li 2 MoO 4 ceramic takes place at ambient temperature during sample pressing and is followed by a postprocessing step at 120°C to remove the residual water from the sample.…”
Section: Introductionmentioning
confidence: 99%